2014
DOI: 10.1017/s0960129513000248
|View full text |Cite
|
Sign up to set email alerts
|

Wadge hardness in Scott spaces and its effectivization

Abstract: We prove some results on the Wadge order on the space of sets of natural numbers endowed with Scott topology, and more generally, on omega-continuous domains. Using alternating decreasing chains we characterize the property of Wadge hardness for the classes of the Hausdorff difference hierarchy (iterated differences of open sets). A similar characterization holds for Wadge one-to-one and finite-to-one completeness. We consider the same questions for the effectivization of the Wadge relation. We also show that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…We will restrict ourselves to the study of the quasi-order ∆ 0 2 (Pω), ≤ w . As mentioned in the Introduction, some results have already been obtained on this quasi-order in [Sel05] and [BG15]. The main result of this article (Theorem 26) comes as a generalization of a construction introduced by Selivanov in [Sel05] that we recall here.…”
Section: Selivanov's Toolboxmentioning
confidence: 82%
See 2 more Smart Citations
“…We will restrict ourselves to the study of the quasi-order ∆ 0 2 (Pω), ≤ w . As mentioned in the Introduction, some results have already been obtained on this quasi-order in [Sel05] and [BG15]. The main result of this article (Theorem 26) comes as a generalization of a construction introduced by Selivanov in [Sel05] that we recall here.…”
Section: Selivanov's Toolboxmentioning
confidence: 82%
“…A tree T ⊆ X < is a set of finite X -sequences closed under the prefix relation. 2 It is well founded if it has no infinite branch, 3 in which case the rank of any t ∈ T is (well) defined by -induction: rk T (t) = 0 if t is -maximal and rk T (t) = sup{rk T (s) + 1 | t s} otherwise. The rank rk(T ) of a nonempty well-founded tree T is the ordinal rk T (∅).…”
Section: General Notationsmentioning
confidence: 99%
See 1 more Smart Citation
“…B Yann Pequignot yann.pequignot@liafa.univ-paris-diderot.fr; yann.pequignot@unil.ch 1 Institut des systèmes d'information, Université de Lausanne, Lausanne, Switzerland 2 LIAFA, Université Paris Diderot -Paris 7, Paris, France importance to Analysis [11], topological spaces that do not satisfy the Hausdorff separation property are central to Algebraic Geometry [6] and to Computer Science [7]. This paper considers without distinction all second countable spaces which satisfy the weakest separation property T 0 , namely every two points which have exactly the same neighbourhoods are equal.…”
Section: Introductionmentioning
confidence: 99%
“…In a more general setting, Schlicht [20] showed that in any non zero dimensional metric space there is an antichain for the qo of continuous reducibility of size continuum consisting of Borel sets. Selivanov ([21] and references there) and also Becher and Grigorieff [2] studied continuous reducibility in non Hausdorff spaces, where the situation is in general much less satisfactory than in the case of the Baire space.…”
Section: Introductionmentioning
confidence: 99%